Modul Pelatihan Pribadi Shiddiq untuk Pengembangan Karakter (Pengembangan Pemikiran Imam Al Ghazali) - Pihasniwati Pihasniwati; Lisnawati Lisnawati; Mayrena Nurwardani (Jurnal Psikologi Integratif, 2016)
This study aimed to find a training model of the of Islamic character development. The honest character was chosen by the researcher because it was called by the researcher as the root of all goodness in the Sahih Hadith of Rasul SAW. The research method consisted of a literature review and expert assessment. On the first phase, the researcher examined the basic concepts of honest morality according to Imam Al Ghazali. Furthermore the researcher developed the concept through the logoanalysis, behavior modification and character education. On the second phase, the component drafting of of Shidiq Personality Training Module was done. On the third phase, the researcher generated a training module guide for trainers. There were four experts who became the informants of the content validity of the training module. The result of the study was a module with a range of the material including The Importance of Being The Honest Personal, honesty in Intentionand Willingness, honesty insaying, honesty indetermination and ambition, honesty in action, honesty in Worship, Skills To Be Honest: Assertive Communication, Being Example of Honesty and the Reflection of the Honesty and the Diary of the Honesty.  The training activities were divided into two parts that were activities inside the session and activities outsidethe session.